The Role of Seasonal Sediment Transport and Sintering in Shaping Titan's Landscapes: A Hypothesis. Issue 8 (25th April 2022) - Lapôtre, Mathieu G. A.; Malaska, Michael J.; Cable, Morgan L.
Abstract: Titan is a sedimentary world, with lakes, rivers, canyons, fans, dissected plateaux, and sand dunes. Sediments on Saturn's moon are thought to largely consist of mechanically weak organic grains, prone to rapid abrasion into dust. Yet, Titan's equatorial dunes have likely been active for 10s–100s kyr. Sustaining Titan's dunes over geologic timescales requires a mechanism that produces sand‐sized particles at equatorial latitudes. We explore the hypothesis that a combination of abrasion, when grains are transported by winds or methane rivers, and sintering, when they are at rest, could produce sand grains that maintain an equilibrium size. Our model demonstrates that seasonal sediment transport may produce sand under Titan's surface conditions and could explain the latitudinal zonation of Titan's landscapes. Our findings support the hypothesis of global, source‐to‐sink sedimentary pathways on Titan, driven by seasons, and mediated by episodic abrasion and sintering of organic sand by rivers and winds. Plain Language Summary: Like Earth, Saturn's moon Titan hosts lakes, rivers, canyons, fans, eroded plateaux, and sand dunes. On Titan, loose solid particles (or sediments) are likely made of soft hydrocarbon grains, prone to rapid breakdown into dust. Yet, Titan's equatorial dunes have been active for up to several hundreds of thousands of years, suggesting that some mechanism must produce sand‐sized particles at these latitudes. We explore the hypothesis that a combination of abrasion, when grains are transported by winds or methane rivers, and sintering, when they are at rest, could produce sand grains that maintain an equilibrium size. Our model demonstrates that seasonal sediment transport could produce sand on Titan and could explain the distribution of Titan's landscapes. Altogether, our findings support the hypothesis of global sedimentary pathways on Titan, driven by seasons, and mediated by episodic abrasion and sintering of organic sand by rivers and winds. Key Points: Long‐lived active dune fields are in apparent contradiction with the predicted rapid abrasion of windblown organic sediment on Titan Episodic abrasion and sintering of organic sediment, driven by seasons, could generate sand with equilibrium sizes on Titan Titan's undifferentiated plains and labyrinth terrains could result from prolonged sintering and diagenesis where transport is infrequent